Primary gastric choriocarcinoma: A case report - Zhang, Xusheng; Yan, Yuke; Meng, Yun; GUO, Huijun; PENG, Jiangshan; DU, Xunqin; Yang, Xiaojun (Frontiers in Surgery, 2022)
Background Choriocarcinoma is a malignant tumour of trophoblastic origin. Most are gestational choriocarcinomas, which usually occur in women with an epithelial origin of the placental chorionic villi and are associated with pregnancy. It mainly originates in the gonads such as the ovaries and testes. However, it rarely occurs in the stomach and is known as primary choriocarcinoma (PGC). Case presentation A 69-year-old man complained of abdominal distention for 3 years, which worsened 1 week later. Gastroscopy showed chronic atrophic gastritis C1 (C1: indicates atrophic gastritis involving the sinus region); the pathology report of the gastroscopic specimen showed high-grade epithelial tumours in the mucosal glands. We diagnosed an occupying lesion in the stomach and performed a laparoscopically assisted distal gastrectomy and Billroth type 1 anastomosis. Postoperative pathology showed “gastric choriocarcinoma with cancerous tissue invading the entire gastric wall”. The patient was discharged on the 11th postoperative day as there were no postoperative complications. The patient was followed up until June 2022 with a good recovery and no recurrence. Conclusion We encountered a case of Primary Gastric Choriocarcinoma, where the cancerous tissue invades the full thickness of the gastric wall.